Investigation on Mechanical and Thermal Properties of a Kenaf/Jute Fiber-Reinforced Polyester Hybrid Biocomposite - Munirah D. Albaqami; Yagya Dutta Dwivedi; N. Krishnamoorthy; M. Logesh Kumar; L. H. Manjunatha; Ch. Mallika Chowdary; Saikh Mohammad Wabaidur; A. Rajendra. Prasad; Rupesh V. Chikhale; S. Praveen Kumar (Advances in Polymer Technology)
This study investigates the mechanical and thermal properties of biocomposite in relation to their hybridization. Compression moulding was utilised to produce hybrid biocomposites composed of polyester resin reinforced with kenaf, jute, and three distinct combinations of kenaf/jute fibers. To increase the bonding of kenaf and jute fibers with polyester resin, a 5 percent NaOH solution was administered to them. The following stacking sequences were used to manufacture a total of five different types of laminates: polyester resin 80 wt%/kenaf fiber 20 wt%, polyester resin 80 wt%/jute fiber 20 wt%), polyester resin 80 wt%/kenaf fiber 5 wt%/jute fiber 15 wt%, polyester resin 80 wt%/kenaf fiber 10 wt%/jute fiber 10 wt%, and polyester resin 80 wt%/kenaf fiber 15 wt%/jute fiber 5 wt%. In the mechanical and thermal tests, it was discovered that the polyester resin 80 wt%/jute fiber 20 wt% biocomposites had increased strength compared to the other hybrid biocomposites investigated.